FACIES AND RESERVOIR-QUALITY VARIATIONS IN THE LATE VISEAN TO BASHKIRIAN OUTER PLATFORM, RIM, AND FLANK OF THE TENGIZ BUILDUP, PRECASPIAN BASIN, KAZAKHSTAN - Collins J.F.; Steffen K.L.; Kenter J.A.M.; Harris P.M.; Kuanysheva G.; Fischer D.J. (My University, 2006)
Tengiz field is an isolated carbonate buildup in the southeastern Precaspian Basin, containing a succession of shallow-water platforms ranging in age from late Famennian to early Bashkirian. Platform backstepping from Tournaisian through late Visean resulted in approximately 800 m (2625 ft) of bathy-metric relief above the Famennian platform. This was followed by as much as 2 km (1.2 mi) of Serpukhovian progradation, which formed a depositional wedge around the older platforms referred to as the Serpukhovian rim and flank. Rim and flank facies include lower slope mudstone, volcanic ash, and platform-derived skeletal packstone to grainstone interbedded with boundstone breccia; middle-slope poorly bedded to massive boundstone breccia with subtypes based on clast composition, size, and packing; upper-slope in-situ microbial boundstone; and outer-platform to shallow-platform skeletal, coated-grain, and ooid packstone to grainstone. The upper-slope microbial boundstone represents the
Keywords: Палеозой::Девонская::Верхний::Фаменский; Палеозой::Каменноугольная::Нижний::Башкирский; Палеозой::Каменноугольная::Верхний::Серпуховский; Палеозой::Каменноугольная::Средний::Визейский; Палеозой::Каменноугольная::Нижний::Турнейский; Paleozoic::Devonian::Upper::Famennian; Paleozoic::Carboniferous::Pennsylvanian::Lower::Bashkirian; Paleozoic::Carboniferous::Mississippian::Upper::Serpukhovian; Paleozoic::Carboniferous::Mississippian::Middle::Visean; Paleozoic::Carboniferous::Mississippian::Lower::Tournaisian